2010
DOI: 10.1166/jnn.2010.1942
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Surface Plasmon Resonance for Silver Particle Film on Mesoporous SiO<SUB>2</SUB> and Soda-Lime Glass During Heating in Air and H<SUB>2</SUB>

Abstract: Thin and thick Ag films on SiO 2 substrates (mesoporous SiO 2 and Soda-lime glass) were respectively prepared by thermal evaporation and spin-coating. The evolution of surface plasmon resonance absorption of the as-prepared samples was investigated when alternately heated in air and H 2 . It has been shown that the evolution behaviours were very different with Ag film thickness and substrates. The results were explained in terms of subtle difference of the two SiO 2 -based substrates in micro-structure or chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Apparently, the efficiency of the removal of Ag þ ions from the film diminishes during HT due to the relatively large thickness of the films studied. A similar result was in fact recently reported by Hu et al 46 in a comparative study on Ag NP oxidation in thin and thick films on mesoporous SiO 2 prepared by thermal evaporation. The authors observed that Ag NPs were not completely oxidized during HT of the thick films in air, which was partially attributed to substrate saturation by Ag þ ions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Apparently, the efficiency of the removal of Ag þ ions from the film diminishes during HT due to the relatively large thickness of the films studied. A similar result was in fact recently reported by Hu et al 46 in a comparative study on Ag NP oxidation in thin and thick films on mesoporous SiO 2 prepared by thermal evaporation. The authors observed that Ag NPs were not completely oxidized during HT of the thick films in air, which was partially attributed to substrate saturation by Ag þ ions.…”
Section: Resultssupporting
confidence: 90%
“…A similar result was in fact recently reported by Hu et al in a comparative study on Ag NP oxidation in thin and thick films on mesoporous SiO 2 prepared by thermal evaporation. The authors observed that Ag NPs were not completely oxidized during HT of the thick films in air, which was partially attributed to substrate saturation by Ag + ions . Similarly, it can be considered herein that the near surface region of the soda glass substrate may become saturated with silver ions in the early stages of HT, therefore, suppressing the ion migration, which is necessary for sustained oxidation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, although subjected to HT in air atmosphere, their sample possessed a relatively large Ag concentration (20.4 at.%). In addition, it is not clear as to the thickness of the films, nor the particular substrate employed, both of which are known to play a role in the processes governing Ag particle transformations [11,12,21], which makes their data difficult to compare. On the other hand, an assessment of the Ostwald growth of Ag NPs in the thick films processed in an inert N 2 atmosphere conducted by our group, yielded an apparent activation energy E R of 2.8 eV [10].…”
Section: Resultsmentioning
confidence: 99%
“…and spacing of the nanocomponents comprising the metal nanostructures. [11][12][13][14][15][16][17][18][19] There is, however, very little work on exploring the possibility of growing self ordered structures using industrially compatible physical vapour deposition (PVD) techniques such as evaporation and sputtering and their variants. Some efforts have been made in this direction using ion beam sputtering.…”
Section: Introductionmentioning
confidence: 99%